TINJAUAN HUKUM ISLAM TERHADAP PENGGUNAAN HARTA PRA PEMBAGIAN WARISAN - Mihfa Wahyuni; Asni Zubair (IAIN BONE, 2020)
AbstractThis research discussed about the heir that used the inheritance before it was distributed. The thing achieved in this research is to find out the cause and impact of the heirs in the Walenreng Village used the inheritance before it was distributed. It also to know the view of Islamic law toward using inheritance before it was distributed. The usefulness of this research expected to give participations and contributions to the development of science in general and Islamic sciencein particular. This research was a qualitative research that used the method sociological approach, theologically normative and normative juridical.The result of this research indicated that some of the heirs in Walenreng Village used the inheritance before it was distributed and the cause was that there was no distribution after the deceased passed away, there was the heir who expected each other to do inheritance distribution, there was the heir who prior pawned the inheritance, and therewas the heir who did not have property. The impact of using inheritance before distribution were that there was no harmonization in the heirs, there was conflict between the heirs, there was the feeling that not considered as family. The view of Islamic law of using inheritance before it was distributed was no allowed because it could make conflict and contrary with hereditary rulesof Islamic law.Keywords: Inheritance; Islamic law; Use Of Inheritance.